Sistema de transporte masivo en la ciudad de Cali: ¿Podrá el municipio financiar el proyecto? - Julio César Alonso Cifuentes; Julieth Alejandra Solano Villa (Estudios Gerenciales, 2006)
This paper investigates the future revenues that Cali´s local government will receive from the tax on gasoline. ARIMA models are used to forecast sales of the different type of gasoline sold in the municipality and these tax revenues. The forecasted tax revenues are used to demonstrate that de Local Government will beable to contribute to the construction of a Massive Transportation System,as it was prearranged in the CONPES 3166 document.